Hard pegs versus intermediate currency arrangements in the Pacific - Matthias Helble; Ahmad Prasetyo; Naoyuki Yoshino (Asian Development Bank Institute (ADBI), 2015)
The 14 Pacific developing member countries (DMCs) of the Asian Development Bank (ADB) have opted for very different exchange rate regimes with varying degrees of flexibility. Whereas several microstates have adopted an external currency as their legal tender, others have decided to use a basket currency and yet others have chosen a managed float. The choice of exchange rate regime can have far reaching economic consequences. In this paper, we first build a simple exchange rate model that illustrates how monetary authorities should best determine the weights of the basket currencies in order to keep fluctuations in gross domestic product (GDP) and in exchange rates to a minimum. We add to the literature by explicitly modeling tourism flows. In the second part of the paper we study the recent developments of the Pacific DMCs in terms of the volatility of their exchange rates, their GDP and their balance of trade. We find that Pacific DMCs with external currencies systematically exhibit lower GDP volatility compared to Pacific DMCs with basket currencies or floats. We conclude that Pacific DMCs with basket currencies or floats seem to have managed their exchange rate with the objective to minimize fluctuations of exchange rates, rather than those of their GDP. Our model therefore provides valuable guidance for those monetary authorities in the Pacific that would like to lower GDP fluctuations.
Keywords: F31; F33; 330; exchange rate policy; economic integration; economic development; microstates